Physical Layer Anonymous Precoding under CSI and Hardware-Imperfections: A KLD-based Approach - Cui, Yifan; Wei, Zhongxiang; Sun, Sumei; Zhu, Xu; Masouros, Christos; Petropulu, Athina P. (IEEE transactions on wireless communications, 2025)
With the emerging privacy sensitive applications, anonymity is recognized as an important attribute in privacy-preserving communications. Existing anonymous precoding approaches at the physical (PHY) layer aim to mask sender's channel characteristic while overlooking the fact that other PHY characteristics contain information that can be traced back to the sender. In this paper, we first reveal that the sender's in-phase and quadrature-phase imbalance (IQI) characteristic of its radio frequency (RF) front end can also be exploited as unique signature of the sender. Since the signal is transmitted through the RF front end and then is propagated through the channel, the received signal carries the composite characteristics of the IQI and channel which can be exploited to identify the sender. To prevent the sender detection enhanced by IQI, an IQI aware anonymous alias sender construction scheme is proposed with the concept of Kullback-Leibler divergence (KLD). It manipulates the signaling of transmitted signal, so that from the perspective of detector, the detection statistic of the real sender is close to that of the alias. To mitigate the communication performance loss caused by the IQI, we exploit the IQI interference as a constructive element. While the constructive IQI design increases the degree of freedom of precoding design, it does not violate the sender anonymity requirement. Finally, an IQI aware anonymous precoder (IAA) is proposed. Simulation demonstrates that the anonymity and communication performance of the proposed IAA precoder is maintained at a high level and is robust to the IQI parameters, where existing approaches fail.